Symptom checklist-90 (SCL-90) in a Thai sample - Tinakon Wongpakaran (2018)
Background: Symptom Checklist-90 (SCL-90) has been used on both normal and clinical samples in Thailand over a long period. However, its validity and reliability have not yet been systemically reported. Objective: Survey the validity and reliability of SCL-90 in a more extensive way, using a normal sample of people throughout Thailand, and investigate the psychometric properties of the Thai version of SCL-90. Material and Method: Four hundred forty eight subjects participated in the present study of which 50.4% were male and with ages ranging from eighteen to 90 years, by providing demographic data and completing the Thai version of SCL-90 and the 16-Personality Factor (16-PF) Questionnaire. The demographic data was analyzed using descriptive statistics, and Cronbach's alpha was used to determine its internal consistency. Factor and confirmatory factor analysis were performed to construct the validity, and convergent and discriminant validities were calculated to generate Pearson's correlation coefficients using the 16-PF subscales. Results: The mean of the global symptoms index was found to be 0.70 + 0.46, with the means of the symptoms ranging from 0.53 for Psychoticism to 0.98 for Obsessive-compulsive disorder. We found to be a significant difference in sub-scales across genders, age groups, geographic regions, educational levels, occupations, and incomes, but the symptom dimension patterns revealed were similar to those of previous studies. Depression and anxiety were the key components to show variance between the normal and clinical samples. The measurements demonstrated good internal consistency with Cronbach's alpha, at 0.97, but did not yield relevant correlations between some of the 16-PF sub-scales, as was expected. Moreover, factor analysis revealed that SCL-90 has a uni-dimensional construct. Conclusion: The Thai version of SCL-90 showed a good internal consistency, but poor discriminant validity with most items occurring for the depression, anxiety and interpersonal sensitivity dimensions. It is recommended that some of the items be revised for clinical studies.